Pengaruh Kepuasan Kerja dan Lingkungan Kerja terhadap Keinginan Keluar Karyawan pada Toko Murah Citra Niaga Samarinda - Purnamasari, Retno; Sanjaya, Arwin; Wediawati, Tuti (Institut Agama Islam Sunan Giri Ponorogo, 2021)
The purpose of this study was to examine the effect of job satisfaction and work environment on the turnover intention of the employees of the Citra Niaga Cheap Store Samarinda. The method used is quantitative. Quantitative research methods can be defined based on the philosophy of positivism to study a particular population or sample. This method uses research tools to collect data. Analysis of quantitative or statistical data aims to test the hypothesis that has been determined with a total sample of 83 respondents from all the population of employees of the Citra Niaga Cheap Store Samarinda. The results of hypothesis testing show that the job satisfaction variable partially has a negative and significant effect on the turnover intention variable. This can be seen from the significance value which is smaller than 0.05, which is 0.000. Thus, hypothesis H1 in this study is accepted. The next hypothesis shows that the work environment partially has a positive and significant effect on the turnover intention variable. This can be seen from the significance value which is smaller than 0.05, which is 0.000. Thus, the research hypothesis H2 is declared accepted. The results of the next test are the variables of job satisfaction and work environment which simultaneously affect turnover intention. This can be seen from the significance value which is smaller than 0.05, which is 0.000 and the Fount calculation shows that Fount (34,217) > Fable (2.72) so that Ho is rejected and Ha is accepted. From the results of the partial analysis, it can be concluded that the job satisfaction variable has a negative and significant influence on turnover intention and the work environment variable has a positive and significant influence on turnover intention. Simultaneously, the variables of job satisfaction and work environment affect turnover intention.